(untitled) (Bioagro, 2020)
The genetic base of irrigated rice in Venezuela, and Latin America, is narrow and the Venezuelan National Project for the Improvement of Genetic Rice (PNMGA) has applied strategies to increase it. The objective of this work was to characterize the genetic diversity of 13 irrigated elite rice lines and four check varieties of economic importance, by means of morpho-agronomical and molecular markers, as well as to determine their association using the Mantel test. A total of 17 genotypes were planted on a trial during the 2014 irrigated cycle in the experimental field of the National Agricultural Research Institute (INIA)-Guárico using a completely randomized block design with three replicates, in a 20 m2-plot with standard agronomical management. Thirteen quantitative characters were evaluated and high variability among genotypes was found. Principal Components Analysis (PCA) showed that four attributes comprised 71 % of the total phenotypic variance. The UPGMA conglomerates analysis for both types of markers using Euclidean and Dice distance allowed the discrimination of the 17 genotypes in five and four groups, respectively, showing that the molecular analysis was more accurate and informative. The multiple correspondence factor analysis indicated that ISSR 880, 834 and 850 markers discriminated the 17 genotypes, and the Mantel test detected a low correlation between distance matrices. Both analyzes contribute to characterize genetic diversity in irrigated rice germplasm.